2021
DOI: 10.3390/catal11080966
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reaction Temperature on the Photocatalytic Activity of TiO2 with Pd and Cu Cocatalysts

Abstract: The aim of this study was to investigate the effects of reaction temperature on the photocatalytic activity of TiO2 with Pd and Cu cocatalysts. N2 sorption, transmission electron microscopy and high-resolution transmission electron microscopy were used to characterize the specific surface area, pore volume, pore size, morphology and metal distribution of the catalysts. The photocatalytic destruction of methylene blue under UV light irradiation was used to test its activity. The concentration of methylene blue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 53 publications
(59 reference statements)
0
29
0
Order By: Relevance
“…The result revealed that Pd/TiO 2 performed well during the photodegradation of methylene blue. [ 28 ] Therefore, the combination of two attractive elements is an efficient way to produce ethanol. Previous studies have demonstrated the various combinations of Pd-Cu nanoparticles that are highly selective and active catalysts for the production of ethanol from CO 2 by thermochemical reaction [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The result revealed that Pd/TiO 2 performed well during the photodegradation of methylene blue. [ 28 ] Therefore, the combination of two attractive elements is an efficient way to produce ethanol. Previous studies have demonstrated the various combinations of Pd-Cu nanoparticles that are highly selective and active catalysts for the production of ethanol from CO 2 by thermochemical reaction [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…As summarized in Table 2 , this conversion rate is above the k app reported for other related systems, with values of 1.1 × 10 –3 ·min −1 for TiO 2 -nanoparticles immobilized within a cellulose nanofibre monolith (MO decomposition) (Lucchini et al 2018 ), or 0.9 × 10 –3 ·min −1 for TiO 2 -nanoparticles immobilized onto a macroporous SiO 2 matrix (MO decomposition) (Marques et al 2021 ). Although larger k values can be obtained by dispersion TiO 2 nanoparticles into the pollutant (71 × 10 –3 ·min −1 for MB under 254 nm irradiation (Chen and Hsu 2021 ). 18 × 10 –3 ·min −1 for MB under 365 nm irradiation (Azeez et al 2018 ), or 2.8 × 10 –3 ·min −1 for MO under UV irradiation) (Zheng et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The dependence of photocatalytic performance on temperature has been widely investigated in the literature, and it is still under debate, with increasing temperature promoting phenomena such as the desorption of adsorbed reactants and the rate of recombination of photogenerated electron/hole pairs that are detrimental for the photocatalysis [24,25]. Otherwise, it is well known that the temperature influences the reaction kinetics, enhancing the activation energy and so speeding the photodegradation process [26,27]. Photodegradation tests using SP fabrics coated with TiO 2 :SiO 2 , under both UV and visible light sources, were compared at three working temperatures: 15 • C, 25 • C (room temperature), and 38 • C. The results are shown in Table 6.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…Under UV LED irradiation, the photocatalytic activity decreases by increasing the temperature, whilst in the case of visible LED, no significant trend was observed. The dependence of photodegradation efficiency by temperature is the result of synergetic (increase in activation energy, increase in charge transfer kinetic) and detrimental effects (the recombination of charge carriers and the altered adsorption equilibrium of reactants such as dye molecules, water, and oxygen) [24,[26][27][28]. Therefore, in this case, the best compromise is working at room temperature, matching environmental and economic requirements [29].…”
Section: Effect Of Temperaturementioning
confidence: 99%